A Method of Instrumental Aerial Observations on Land Ice in the Sea (Spasob Instrumentalnykh Avyanablyudenii nad Materikovmi Ldami v More) - Betin,V. V.; Zhadrinskii,S. V.; Uralov,N. S. (1961)
The measurement of the size and height of icebergs, and also huge hummocks and stamukhi, by means of an aerial perspective angle measuring instrument is discussed and the degree of accuracy in the measurements is determined. Also the advantages of the method in aerial reconnaissance flights is pointed out. (Author) Trans of Meteorologiya i Gidrologiya (USSR) n5 p51-54 1959, by M. Slessers. Also available as TT-61-28006.